MENGUKUR DAYA PAKSA HUKUM DALAM ISLAM - Holirur Rahman (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2010)
The main characteristic of a law is capacity to force includedIslamic law. Islamic law has God (rabbaniyah) as its source topeople (insâniyah), that all aspects related with peopleconcerned by Islamic law. When Islamic law is in confrontrationwith nation context, so a khilafah or a power that sides with thebenefit and avoids kemafsadatan. It is the first and main purposeof force capacity in Islamic law. Dialectical thinking about Islamin substantif and formality becomes the irrefutable reality. Thefirst way to make Islamic law becomes rahmatan li al-‘âlamînin isactualization from Islamic law that becomes a togethernessincreases people life to be better in all domain both internal andexternal domain.